Respuesta :

equation of f(x)

point of intersection of f(x) and x axis - (-4,0)

point of intersection of f(x) and y axis - (0,4)

Equation y = x +4

g(x) = f( kx)

= kx +4

g(-2) = -2

-2k +4= -2

-2k = -2 -4

-2k = -6

k= 3

Using the graph, it is found that k = 3.

-----------------------------

  • When the x-axis is -6, function f is -2. Thus, [tex]f(-6) = -2[/tex].
  • By the same logic, for function g, [tex]g(-2) = -2[/tex].
  • We have that [tex]g(x) = f(kx)[/tex], and from the above bullet-points, we have that [tex]g(-2) = f(-6)[/tex]. Thus:

[tex]-2k = -6[/tex]

[tex]2k = 6[/tex]

[tex]k = \frac{6}{2}[/tex]

[tex]k = 3[/tex]

A similar problem is given at https://brainly.com/question/24753049

ACCESS MORE